CONTRASTIVE ANALYSIS OF PARTICLES IN CHINESE AND INDONESIAN LANGUAGE - Qin Xiao; Pratomo Widodo (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
In Chinese and Indonesian, particles are often used and occupying an important place specifically in daily conversation. The study distinguishes ways of using particles in order to propose suggestions that can be useful for Chinese learners in Indonesia. In this article, the author describe the four pairs of particles to compare the similarities and differences in terms of syntax, semantics, pragmatics and analyzing the types and reasons in particle’s using error for Indonesian learners based on corpus HSK. Where the data sources are the examples of a sentence containing particles, the technique of data collection is the technique of reading and taking notes, and the instrument is a human instrument. The authors found that the four pairs of particles have similarities and differences in syntax, semantics and pragmatics: all of them can be used at the end and middle of the sentence, but not all can be used with other particles; all the pairs can translate to one another and can also be translated into other particles or adverbs, but there are some particles sometimes don’t need to be translated; in different contexts, the four pairs of modal particles have different pragmatic functions. Keywords: particle, Chinese, Indonesian, contrastive analysis